Pendekatan Culturally Responsive Teaching (CRT) dalam Pembelajaran Sejarah Tingkat Lanjut pada Pelajaran Revolusi Perancis & Revolusi Amerika di SMA Negeri 4 Pematang Siantar - Sihombing, Imam Daniel; Ismiatun, Novi (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Culturally responsive teaching or CRT in Advanced History subjects is one of the most challenging subjects to make history subjects become vivid in the class, especially when the students in a school are multi ethnic or multicultural. The Purpose of the research is to give the alternative way or sample of one lesson related between culturally responsive teaching and the subject to become easier to understand by the students. The method of the research is literature research and qualitative approach, which answers how a culturally responsive teaching approach can connect with advanced history subjects, so the lesson will be plausible to the students. The result shows that  culturally responsive teaching in social science class and the class whom using Merdeka Curriculum can be related in daily life of students especially from their tribe or tradition in SMA Negeri 4 Pematang Siantar, where advanced history is stereotyped as international history could using the local wisdom. So the students could be connected in an emotional way regarding history lessons which will be taught by the teacher. SMA Negeri 4 Pematang Siantar is school with multi-ethnic, where the school is dominated with Simalungun Culture, Which could apply  culturally responsive teaching in history lesson, so the students will know about the diversity of culture and their own culture to be connected with it, especially when it comes to advanced history subject in senior high school in the school.